PERAN MEDIASI SIKAP PADA PENGARUH KEPERCAYAAN MEREK TERHADAP PERSEPSI KULINER HALAL (Studi Pada Mahasiswa dan Dosen Institut Islam Mamba'ul 'Ulum Surakarta) - S Sulistyowati; B Baehaqi (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
This study aims to determine: 1) Analyzing the effect of brand trust on consumer attitudes towards halal culinary products. 2) Analyzing the influence of brand trust on Halal Label Perception of halal culinary. 3) Analyzing the influence of consumer attitudes on the Perception of the Halal Label of Halal Culinary. 4) Analyzing consumer attitudes in mediating the influence of brand trust on Halal Label Perception of halal culinary. This type of research is quantitative research. The population in this study are students and lecturers of the Islamic Institute of Mamba’ul ‘Ulum Surakarta. The sample in this study was taken to facilitate research from the large number of populations, the sample selection can be seen in the sampling technique, the number of samples in this study were students and lecturers of the Islamic Institute of Mamba’ul ‘Ulum Surakarta. The sampling technique used in this study is a non-probability method because it uses an accidental sampling technique. Research Results: 1) Brand Trust has a positive and significant effect on consumer attitudes of Halal Culinary products. This means that the Brand Trust felt by consumers on Halal Culinary products can increase the Perception of the Halal Label on these products. These results show that the better the brand trust felt by consumers, it has a positive influence on consumer attitudes towards halal culinary products. 2) Brand trust has a positive and significant effect on satisfaction with halal culinary purchases. This means that the brand trust felt by consumers in halal culinary products can increase purchase satisfaction for these products. These results show that the better the brand trust felt by consumers in halal culinary products, the higher the satisfaction of purchasing these halal culinary products. 3) Consumer attitudes have a positive and significant effect on buyer satisfaction of halal culinary products. This means that consumer attitudes perceived by consumers on halal culinary products can increase buyer satisfaction for these products. This shows that the higher the attitude of consumers perceived by consumers on halal culinary products, the higher the satisfaction of buyers with these products. 4) Consumer attitudes mediate positively and significantly affect brand trust on purchase satisfaction of halal culinary products, in other words, consumer attitudes affect Halal Label Perception through brand trust. The better the perceived buyer satisfaction, the higher the brand trust which will increase the perception of the halal culinary label.